Systemic sclerosis and hyperthyroidism in pregnancy - Awalia Awalia; Yuliasih Yuliasih; Joewono Soeroso (Indonesian Journal of Rheumatology, 2013)
Systemic sclerosis (SSc) is a connective tissue disease affecting women of childbearing age at least five times more than men. For a long time, pregnant women with SSc have high morbidity and mortality based on case reports and case series. Therefore, the disease was a contraindication for pregnancy. However, current retrospective studiesshow that despite of an increased frequency of prematurity and small for gestational age infants, overall maternal and neonatal survival is good. With close monitoring and appropriate therapy, most scleroderma patients can sustain a successful pregnancy.